The Association Between Quarantine Duration and Psychological Outcomes, Social Distancing, and Vaccination Intention During the Second Outbreak of COVID-19 in China - Lele Chen; Dingding Wang; Yuxin Xia; Renlai Zhou (Frontiers Media S.A., 2022)
Objectives: To examine the association between quarantine duration and psychological outcomes, social distancing, as well as vaccination intention during the second outbreak of COVID-19 in China.Methods: A cross-sectional online survey was conducted in January 2021. Participants were invited to complete the measurement of quarantine duration, social distancing, psychological distress, wellbeing (WHO-5), and vaccination intention. Multiple linear regression and logistic regression were performed to examine the relationship between quarantine duration and psychological distress, wellbeing, social distancing, and vaccination intention.Results: Of the 944 participants, 17.2% of the participants experienced quarantine. Quarantine for 1-7 days increased the social distancing (β = 2.61 95% confidence interval (CI) 1.90-3.33) and vaccination intention (OR = 2.16 95% CI 1.22-3.82). Quarantine for >7 days was associated with the increased social distancing (β = 3.00 95% CI 2.37-3.64) and psychological distress (β = 1.03 95% CI 0.22-1.86), and decreased wellbeing (β = 1.27 95% CI 0.29-2.26).Conclusion: Longer quarantine duration showed increased social distancing, increased psychological distress, and decreased wellbeing. Quarantine for 1-7 days was associated with increased vaccination intention.